How the use of business intelligence tools in the fistula sector can improve surgical performance - Cochran, Seth (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: The aim of Operation Fistula’s ongoing work is to incentivize our partnering clinical teams by providing performance-based funding. We do this using a coordinated chain of business intelligence tools, and by sharing detailed customized visual dashboards so they can track both patient outcomes and surgical performance. We have repurposed a number of leading business intelligence tools to create a patient tracking and performance management system. This platform combines several technologies to collect, store, and analyze data, which we communicate with our partners. Methods: In order for data to be collected into our system, our partner surgeons and nurses input patient data directly into customized, standardized, electronic forms on a tablet or phone. Results are uploaded in real time, and feed into the data visualization software. Our London-based team is then able to create data visualization dashboards, based on the collected data, which are shared with stakeholders in our partnering countries. Results: We are tracking surgical outcomes using our mobile data collection and visualization programmes. We are also measuring the impact of the digital performance-based funding model, currently being used in the SAVA region in Madagascar. Our partnering clinical teams have responded positively to the introduction of our system, which we have found to ensure quality standards of care. Conclusions: The initial phase of this work has yielded positive results. We have seen increased engagement and motivation from our partnering clinical staff, which exemplifies how both a performance-based funding system, and access to digestible data, can improve surgical performance.